Accuracy of anterior nasal swab rapid antigen tests compared with RT‐PCR for massive SARS‐CoV‐2 screening in low prevalence population. Issue 2 (6th December 2021) - Jakobsen, Kathrine Kronberg; Jensen, Jakob Schmidt; Todsen, Tobias; Kirkby, Nikolai; Lippert, Freddy; Vangsted, Anne‐Marie; Klokker, Mads; von Buchwald, Christian
Abstract : The aim was to determine the accuracy of anterior nasal swab in rapid antigen (Ag) tests in a low SARS‐CoV‐2 prevalence and massive screened community. Individuals, aged 18 years or older, who self‐booked an appointment for real‐time reverse transcriptase‐polymerase chain reaction (RT‐PCR) test in March 2021 at a public test center in Copenhagen, Denmark were included. An oropharyngeal swab was collected for RT‐PCR testing, followed by a swab from the anterior parts of the nose examined by Ag test (SD Biosensor). Accuracy of the Ag test was calculated with RT‐PCR as reference. We included 7074 paired conclusive tests ( n = 3461, female: 50.7%). The median age was 48 years (IQR: 36–57 years). The prevalence was 0.9%, that is, 66 tests were positive on RT‐PCR. Thirty‐two had a paired positive Ag test. The sensitivity was 48.5% and the specificity was 100%. This study conducted in a low prevalence setting in a massive screening set‐up showed that the Ag test had a sensitivity of 48.5% and a specificity of 100%, that is, no false positive tests. The lower sensitivity is a challenge especially if Ag testing is not repeated frequently allowing this scalable test to be a robust supplement to RT‐PCR testing in an ambitious public SARS‐CoV‐2 screening.